1998
DOI: 10.1055/s-1998-1738
|View full text |Cite
|
Sign up to set email alerts
|

Diels-Alder Reactions of α,β-Unsaturated Thioesters and α,β-Unsaturated Selenoesters

Abstract: α,β-Unsaturated thioesters and selenoesters serve as dienophiles in Diels-Alder reactions with a variety of 1,3-dienes. Good levels of regioselectivity are obtained with unsymmetrical dienes when Lewis acid promoters are used. Thioesters and selenoesters are more reactive than the corresponding methyl esters based on competition experiments with cyclopentadiene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…This new reaction obviously provides a convenient entry into selenoesters of various substituted 4-cyclohexene carboxylic acids. 144 …”
Section: Acyl Radicals From Selenoesters (Acyl Selenides) (Rco−ser′)mentioning
confidence: 99%
“…This new reaction obviously provides a convenient entry into selenoesters of various substituted 4-cyclohexene carboxylic acids. 144 …”
Section: Acyl Radicals From Selenoesters (Acyl Selenides) (Rco−ser′)mentioning
confidence: 99%
“…The intermolecular Diels-Alder reaction of 5 with 6 was carried out with Et 2 AlCl as the catalyst, [12] and ketone 7 was obtained in 65 % yield. and treatment of 8 with KHMDS in THF and subsequent reaction with O 2 in the presence of P(OMe) 3 [13] gave a tertiary alcohol in 75 % yield. Thus, vinyl silyl ether 9 was obtained in 95 % yield after reaction of the tertiary alcohol with TESOTf and 2,6-lutidine in CH 2 Cl 2 .…”
mentioning
confidence: 99%
“…We then studied the Diels–Alder reactions of 2 . Hart et al 12. had shown that selenoacrylates are much more reactive than normal acrylates, presumably owing to poorer overlap between the selenium atom and the carbonyl group, thereby making the carbonyl group more ketone‐like rather than ester‐like.…”
Section: Methodsmentioning
confidence: 99%